Innovation platforms for Climate Smart Agriculture in Honduras - Muller, Christian; Salgado, Ricardo; Duron, Marlon; Le Coq, Jean-François; Varax, Magali de; Gamba-Trimiño, Catherine; Howland, Fanny C.; Chia, Eduardo; Gallardo, Omar; Andrieu, Nadine (2018)
Innovation Platforms for the adoption of Climate Smart Agriculture for Family farmers (PIASAC) was a project aimed at creating local knowledge and capacities on climate change and finding options for adaption in a participatory way. The project took place in the municipality of Gracias, located in the dry corridor of Honduras. 38 farming families were involved in a 2-year research process facilitated by the Direction of agricultural science and technology (DICTA), with the methodological support of CIRAD under the coordination of CIAT. The project was funded by FONTAGRO.